Imperfect messengers? An analysis of vaccine confidence among primary care physicians. Issue 18 (20th April 2022) - Callaghan, Timothy; Washburn, David; Goidel, Kirby; Nuzhath, Tasmiah; Spiegelman, Abigail; Scobee, Julia; Moghtaderi, Ali; Motta, Matthew
Highlights: 10.1% of primary care physicians (PCPs) do not agree vaccines are safe. 9.3% of PCPs do not agree that vaccines are effective. 8.3% of PCPs do not agree that vaccines are important. Physician confidence in COVID-19 vaccines varies across vaccines. A troubling proportion of PCPs lack high levels of vaccine confidence. Abstract: Background: Growing narratives emphasize using primary care physicians as leaders in efforts to promote COVID-19 vaccination among the vaccine hesitant. Critically however, little is known about vaccine confidence among primary care physicians themselves. The objective of this study was to assess both physician confidence that in general, vaccines are safe, effective, and important, as well as physician confidence in each COVID-19 vaccine in the United States. Methods: We rely on data from a national survey of primary care physicians conducted from May 14-May 25, 2021. We assess the influence of demographic, social, and political factors on physician beliefs that in general, vaccines are safe, effective, and important, as well as physician confidence in the safety of the Moderna, Pfizer, and Johnson & Johnson COVID-19 vaccines. Results: 10.1% of primary care physicians do not agree that, in general, vaccines are safe, 9.3% do not agree they are effective, and 8.3% do not agree they are important. While 68.7% of physicians were 'very confident' in the safety of the Moderna vaccine and 72.7% were 'very confident' in the safety of the Pfizer vaccine, only 32.1% of physicians were 'very confident' in the safety of the Johnson & Johnson COVID-19 vaccine. Conclusion: A troubling proportion of primary care physicians lack high levels of vaccine confidence. These physicians may not be well positioned to actively promote COVID-19 vaccination even as political and media narratives push physicians to lead this effort. Interventions aimed at improving vaccine confidence among some physicians may be needed so that all physicians can fulfill needed roles as trusted vaccine communicators.